1990
DOI: 10.1073/pnas.87.19.7747
|View full text |Cite
|
Sign up to set email alerts
|

2'-O-alkyl oligoribonucleotides as antisense probes.

Abstract: ABSTRACT2'-O-Methyl oligoribonucleotides have recently been introduced as antisense probes for studying RNA processing and for affinity purification of RNA-protein complexes. To identify RNA analogues with improved properties for antisense analysis, 2'--alkyl oligoribonucleotides were synthesized in which the alkyl moiety was either the threecarbon linear allyl group or the five-carbon branched 3,3-dimethylallyl group. Both these analogues were found to be completely resistant to degradation by either DNA-or R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
55
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 8 publications
3
55
0
1
Order By: Relevance
“…The sequences prepared (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) are shown in Table 1. Average coupling yields for dimer incorporation were -90% as assessed by the trityl assay method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences prepared (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) are shown in Table 1. Average coupling yields for dimer incorporation were -90% as assessed by the trityl assay method.…”
Section: Resultsmentioning
confidence: 99%
“…Following chain assembly, the oligonucleotides were cleaved from the support, deprotected and purified as previously described (9). The single absorption band on polyacrylamide gel found for each oligomer indicated their high purity (>95%) and the retarded mobility of the sulfide containing oligomers (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) relative to the unmodified sequence (5) (9). How do we account for: (i) the general destabilizing effect of (3'-CH2-CH2-S-CH2-5') linkages, and (ii) for the discriminatory binding properties of sulfide strands containing 2'-substituted (OH and OMe) sugars?…”
Section: Resultsmentioning
confidence: 99%
“…Equal amounts (2-4 g) of poly(A) RNA from both reference and experimental samples were used as templates to synthesize fluorescently labeled cDNA probes for hybridization to the microarrays. The RNA was reverse transcribed in the presence of 5-(3-aminoallyl)-2Ј-deoxyuridine 5Ј triphosphate (18). The reference sample was coupled to fluorescent dye (Cy)3, and the experimental sample was coupled to Cy5.…”
mentioning
confidence: 99%
“…Results from a number of laboratories have shown that oligonucleotides which contain 2'-0-alkyl substituents, such as 2'-0-methylribose, form very stable duplexes with complementary RNA target molecules (12)(13)(14)(15)(16). The improved binding constants observed with oligo-2'-O-methylribonucleotides and the enhanced nuclease resistance of the phosphorothioate or methylphosphonate oligomers could be used to advantage to design effective antisense oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%